The Effects of Dosed versus Gravity‐Fed Loading Methods on the Performance and Reliability of Contour Trench Disposal Fields Used for Onsite Wastewater Treatment. Issue 2 (1st March 2013) - Bridson‐Pateman, Evan; Hayward, Jennifer; Jamieson, Rob; Boutilier, Leah; Lake, Craig
Abstract : In Nova Scotia, Canada, contour trench disposal fields are the most common type of onsite wastewater system. In this study, two identical contour trench disposal fields were monitored for 3 yr to compare performance under gravity‐fed versus periodically dosed loading conditions. Influent and effluent from both systems were analyzed for a suite of water quality parameters, and the hydraulics of the systems were assessed using tracer studies and measurements of ponded water depth in the distribution trenches. Ponded water depths in the distribution trench of the gravity‐fed disposal field were observed to increase steadily during the monitoring period, indicating progressive clogging. This was not observed in the periodically dosed field. Regarding treatment, both systems performed well, consistently producing effluent with 5‐d biochemical oxygen demand and total suspended solids (TSS) concentrations <10 mg L −1 and achieving >5 log reductions in Escherichia coli . However, the gravity‐fed system produced statistically lower average effluent concentrations for total P and TSS. It is speculated that the slightly better treatment performance achieved by the gravity‐fed system is due to enhanced biomat formation. This study demonstrated adequate treatment of residential wastewater by contour trench disposal fields regardless of loading method. However, because the hydraulic performance of these systems is heavily dependent on pretreatment and loading methods, it is recommended that a dosing system be used to distribute wastewater to contour trench disposal fields to help prevent hydraulic failure.